Damage to the pilot balloon of the nasotracheal tube during orthognathic double-jaw surgery: A case report - Kim, Eun-Jung (J Dent Anesth Pain Med, 2015)
In oral and maxillofacial surgery, many complications associated with nasotracheal tube can be caused. In this case, we reported ballooning tube damage of nasotracheal tube during orthognathic double-jaw surgery and replacement of tube through cut down of tube and tube exchange using airway exchange catheter. The patient scheduled for high Le Fort I osteotomy and bilateral sagittal split osteotomy was intubated nasotracheally with nasal endotracheal tube. During maxilla osteotomy, air bubble was detected in the oral blood. In spite of our repeated ballooning, the results were the same so we changed damaged tube using airway exchange catheter aseptically. Tiny and superficial cutting site was detected in the middle of pilot tube. As we know in our case, tiny injury impeded a normal airway management and prevention is important.